Intricate Transcriptional Networks of Classical Brown and Beige Fat Cells - Park, Jun Hong; Hur, Wonhee; Lee, Sean Bong (Frontiers in Endocrinology, 2015)
Brown adipocytes are a specialized cell type that is critical for adaptive thermogenesis, energy homeostasis and metabolism. In response to cold, both classical brown fat and the newly identified “beige” or “brite” cells are activated by β-adrenergic signaling and catabolize stored lipids and carbohydrates to produce heat via UCP1 (Uncoupling protein 1). Once thought to be non-existent in adults, recent studies have discovered active classical brown and beige fat cells in humans, thus reinvigorating interest in brown and beige adipocytes. This review will focus on the newly discovered transcription factors and microRNAs (miRNAs) that specify and orchestrate the classical brown and beige fat cell development.